(untitled) (Revista Latino-Americana de Enfermagem, 2010)
This study aimed to evaluate the association between psychological demands and control on work and the occurrence of musculoskeletal disorders among nursing workers. This cross-sectional study involved 491 nursing workers from a University hospital in Rio Grande do Sul. Brazilian versions of the Nordic Musculoskeletal Questionnaire and the Job Content Questionnaire were used. Among the participants, 96.3% reported some pain in any given part of the body last year, 73.1% in the last seven days and 65.8% reported difficulty in their daily routine. The chances of shoulder pain (OR=1.97; CI95%=1.07-3.64), in the thoracic spine (OR=1.83; CI95%=1.02-3.35) and in the ankles (OR=2.05; CI95%=1.05-4.02) were higher in the high work demand quadrant when compared to the low demand quadrant, after adjustments for potentially confusing factors Intervention measures in the organizational structure are needed, redefining demand levels and control at work.